Water deficit in common beans. III. Maximum, crop evapotranspiration and its relationship with evapotranspiration by the Penman method and "class A" pan evaporation. - Bergamaschi, Homero; Vieira, Hamilton J.; Libardi, Paulo L.; Ometto, José C.; Angelocci, Luiz R. (Pesquisa Agropecuaria Brasileira, 2014)
Maximum evapotranspiration (ETn) of common beans (Phaseolus vulgaris L.) and its relationship with evapotranspiration calculated by the Penman method (Kc1 = ETm/ETo) and non corrected "class A" pan evaporation (Kc2 = ETm/Eo) were quantified in a field experiment conducted at Piracicaba, SP, 22º43'30" south latitude and 576 m altitude, in 1983. Common beans cv. Aroana 80, type 1 (CIAT classification) was sown in three planting dates: July 7, July 22 and August 4. Maximum crop evapotranspiration was calculated by the soil water balance method, in a split-plot design, in plots of 30 m x 20 m, with soil water potential over -0,05 MPa during all the crop cycle. Mean ETm al 3,8 mm.day-1 and total ETm al around 360 mm occurred from sowing to physiological maturity. However, ETm increased from 2,4 mm.day-1 at the sowing-emergence period to 5,0 mm.day-1 during flowering. Early in the crop cycle, Kc1 and Kc2 coefficients were around 0.6 and 0,5, increased up to 1,4 and 1,1 by flowering, and decreased to the initial values by the end of the grain filling period. Mean Kc coefficients of each subperiod were highly correlated with mean values of leaf area index (L). Quadratic mathematic models, with negative constant for the L2 term, appeared to estimate better the Kc variations in response to the L variations.